The development of a project-based student worksheet to foster fourth graders' creativity in integrated theme learning - Sofyan Aris; Alben Ambarita; Rochmiyati Rochmiyati (Lighthouse Publishing, 2022)
The goal of this study was to find out if a student worksheet, which was based on project-based learning, was valid in terms of improving learning outcomes. Research and development (R&D) was employed as the method, which was carried out until the initial product design development stage. Purposive sampling was employed involving 22 students in class IV at SD Negeri 7 Metro Barat as the experimental class and 23 students in class IV at SD Negeri 3 Metro Barat as the control class. A validation questionnaire was utilised to collect data. The percentage method and descriptive analysis were utilised in the data analysis. The project-based learning student worksheet was declared valid to improve learning outcomes based on the results of an expert validation test (87.5%) on content, an expert validation test (80%) on construction, and an expert validation test (100%) on language. The implications of the findings are also discussed along with suggestions for further research.